English English - Istiqomah, Khazanah; Sipahutar, Herbert (Universitas Negeri Jakarta, 2025)
The low level of learning activities, analytical thinking skills, and student learning outcomes are indications of the need to improve the quality of learning through the implementation of innovative learning that makes students active subjects of learning in an effort to develop 21st century skills that are very important for students in facing the rapid development of science and technology today. This research aims to determine the effect of the PBL model assisted by student worksheets on learning activities, analytical thinking skills, and cognitive learning outcomes of class XI students at one of SMA Negeri in Medan City on the human immune system material. This material is very suitable for PBL because it contains complex biological processes and various disorders that involve the role of various components of the body. This research is a quasi-experimental research with a non-equivalent pretest-posttest control group design. Samples were obtained through class randomization until 2 classes were obtained, where 1 class was an experimental class and 1 class was a control class. The data obtained were analyzed using an independent sample t-test which showed a significance value lower than 0.05. Students in the experimental group showed higher learning activity (78,53 > 64,47), better analytical thinking skills (77,88 > 70,32), and higher cognitive learning outcomes (81,91 > 70,44) compared to the control class. Thus, it can be concluded that the PBL model assisted by student worksheets has a significant effect on learning activities, analytical thinking skills, and cognitive learning outcomes of class XI students.